Determination Analysis of Sediment Retention Dam Location based on Erosion Hazard Level with ArcGIS program (Case Study In The water catchment area of Marangkayu Reservoir). - Tomy Wahyudi Utomo; Muhammad Sumaryono, Yohananes Budi Sulistioadi (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
This research aims atthe authors will analyze erosion rate per year, erosion class, erosion hazard in the water catchment area of Marangkayu Reservoir using the Universal Soil Loss Equation (USLE) method and determine which locations are potential to be constructed of check dam into the water catchment area of Marangkayu reservoir optimally.The results of erosion calculation 1) program obtain the value of soil erosion occurring in the water catchment area of Marangkayu Reservoir that is 863.8 tons per hectares per year of total land area 13,489.392 hectares.2) Classification of erosion class based on the value of erosion of land occurring in the Largest water catchment area Marangkayu Reservoir is class III of 6,744.55 ha or 50.15%, Class II 3.596.35 ha or 26.74%, Class IV area of 3.101.42 ha or 23.06% and the smallest in class I area of 6.06 ha or 0, 05% of the total water catchment area of Marangkayu reservoir. 3) While the Classification of Erosion Hazard Level based on erosion class and depth of soil solum in water catchment area of Marangkayu Reservoir with highest Erosi Hazard Level is found on Medium Class Dangerous Medium level of 4,260.15 ha or 31,75%, Level Higher Erosion grade 3.580, 43 ha or 26.68%, Heavy Danger Level grade Weight of 3.102.25 ha or 23.12%, High Speed Erosion Health grade 2.469.92 ha or 18.41% and Erosi Hazards Levels with Very Lightweight grade of 6 , 06 ha or 0, 05% of the total water catchment area of Marangkayu reservoir.4) From the analysis, there are 295 Units of water catchment area that are suitable for the construction of Sedimentary Rocks (Check Dam) with a total area of 4,918 hectares.